Relation between Preoperative vitamin D level and Post operative Infection in Patient undergoing Pancreaticoduodenectomy (Whipple’s) procedure (Journal of Shaheed Suhrawardy Medical College, 2024)
The patient who underwent pancreaticoduodenectomy operation suffers from obstructive jaundice sometimes. Due to lack of bile in intestine these patients have difficulty in absorption of fat soluble vitamin A, D, E and K. Vitamin D has an important role in maintenance of our immune system. So patients who have low serum vitamin D level suffer from infection more than those with normal level in postoperative period. This study aims to identify vitamin D deficiency among patients suffering from obstructive jaundice and see whether they suffers more postoperative infection and hospital stay. In this observational study 13 patients were enrolled after considering the exclusion and inclusion criteria who underwent pancreaticoduodenectomy operation but have low vitamin D level in the department of Hepatobiliary, Pancreatic and Liver transplant Surgery for one year period. Another 13 patients were selected who has normal vitamin D level. They were leveled into two groups. Group one had normal vitamin D level and group two have low vitamin D level. After operation superficial surgical site infection, deep surgical site infection, pneumonia, bile leak, pancreatic fistula, hospital stay were recorded. CRP level were measured on 3rd, 5th and 7th POD. Data analysis to calculate the significance between two groups were done by using SPSS version 23. P value was regarded significant if